Vox Populi Essays in the History of an Idea - Boas, George (Johns Hopkins University Press, 2020)
Originally published in 1969. The proverb vox populi, vox Dei first appeared in a work by Alcuin (ca. 798), who wrote that "the people [] are to be led, not followed. [] Nor are those to be listened to who are accustomed to say, 'The voice of the people is the voice of God.'" Tracing the changing meaning of the saying through European history, George Boas finds that "the people" are not an easily identifiable group. For many centuries the butt of jokes and the substance of comic relief in serious drama, the people became in time an object of pity and, later, of aesthetic appeal. Popular opinion, despised in ancient Rome, was something sought, after the French Revolution. The first essay documents the use of the titular proverb through the eighteenth century. In the next six essays, Boas attempts to determine who the people were and how writers and philosophers have regarded them throughout history. He also examines the people as the creators of literature, art, and music, and as the subject of others' artistic representations. In a final essay, he discusses egalitarianism, which has given a voice to the common person. Animating Boas's account is his own belief in the importance of the individual's voice-as opposed to the voice of the masses, which is by no means necessarily that of God or reason.